La sidérurgie chez les Sénons : les ateliers celtiques et gallo-romains des Clérimois (Yonne) - Dunikowski, Christophe; Cabboi, Sandra (Documents d'archéologie française, 1995)
Discovered during the construction of the A5 motorway, the early metalworking site of the Clérimois (Yonne) delivered the remains of some ten workshops which produced iron between the 4th century B.C. and the 5th century A. D. The published results are many: descriptions and typologies of the structures (18 furnaces studied), anthracology and analyses of the ores and slags. The study of the forges has allowed an estimation of the overall production: 5 000 tonnes of iron from 15 500 tonnes of smelted ore. Four fifths of this iron was produced between the end of the La Tène period and the 2nd century A.D. by large furnaces equipped with systems for removing the slag. These data can already be considered as a reference in the study of ancient metallurgy.